Moderate Factors of Work Discipline on Employee Performance at an Information Technology Consulting Company in Jakarta - Wachyu Hari Haji; Muhammad Syahidin (Budapest International Research and Critics University, 2022)
The purpose of the research is to analyze moderate factors of work discipline on employee performance at an Information Technology Consulting Company in Jakarta. The approach used in this research is quantitative, with explanatory methods, more specifically causality associative. The research unit is all employees of PT Naghayasha Rahardja in various units, as many as 180 employees. The results of hypothesis testing use the T-statistic and P-value in the bootstrapping algorithm report. The results show that work discipline has a positive and significant effect on employee performance. Leadership has no significant effect on employee performance. Organizational culture has a positive and significant effect on employee performance. Leadership moderates the relationship between work discipline and employee performance. Organizational culture moderates the relationship between work discipline and employee performance.